Aplikasi Penentuan Jumlah Pinjaman USP (Usaha Simpan Pinjam) Bantan Jaya Berbasis Web - Surya Darma; Rezki Kurniati (LPPM Institut Pendidikan Nusantara Global, 2026)
The rapid development of information technology has encouraged digital transformation in microfinance institutions, including Savings and Loan Enterprises (USP); however, most existing systems primarily focus on transaction recording and administrative efficiency without integrating structured financial feasibility analysis into loan amount determination. This study aims to design and develop a web-based loan determination system at USP Bantan Jaya that integrates field survey data and the Utilization Business Plan (RUP) into an automated calculation model incorporating net income analysis, installment capacity (set at 50% of net income), and risk adjustment factors based on historical arrears ratios. The novelty of this research lies in the integration of measurable financial parameters and risk-based adjustment into a structured decision-support mechanism supported by Role-Based Access Control (RBAC) to ensure data security and access control. Functional testing using the black box method demonstrated a 100% success rate across nine core system features, while simulation results showed that the system standardized loan eligibility calculations and adjusted loan disbursement up to 60% of the initial application based on risk assessment. These results indicate that the proposed system enhances decision consistency, transparency, and accuracy in determining loan amounts, providing a practical and replicable model for more professional and sustainable USP management.